Exploring Regional Differences in Cultural Values : A Hybrid Thematic Analysis - Choudhary, Jugal; Shree, Sonal; Rastogi, Shailesh; Kappal, Jyoti (Prabandhan: Indian Journal of Management, 2022)
Purpose : Extant research had, for the most part, confined itself to comparing cultural values at the inter-nation level. This was despite the criticism from studies such as Hofstede’s and the knowledge that most variation in culture resided within nations and not between them. Moreover, the alarming failures of cross-border mergers and acquisitions and other challenges that organizations ascribed to cultural differences pointed to the need for more utilitarian knowledge in this field. Hence, this study sought to explore the cultural differences within a diverse and developing nation, in this case, within India, that were relevant to organizations. Design/Methodology/Approach : This paper drew on 30 in-depth interviews with senior executives in multiple sectors with organizational experience in more than one region of India. Interview transcripts were analyzed with the help of open coding, followed by clustering into higher-order themes. Finally, a hybrid thematic analysis was used to develop the themes/values. Findings : Interviewed executives reported having experienced differences in cultural values when working with different regions of India. Mastery, Egalitarianism, Embeddedness, and Hierarchy were the second-order values that over two-thirds of the executives experienced as different. Originality/Value : This knowledge could be of great value, particularly to organizations outside India planning to enter or expand in India and organizations within the country planning to expand beyond their current location.